The associativity to articulate productive chains in Colombia: The case of small Creole potato producers in Subachoque, Cundinamarca - Vargas Prieto, Amanda; Fajardo Rodríguez, Cindy Lorena; Romero Rodríguez, Yesica Estefanía; Nieves Forero, Karen Yiseth (Cooperativismo & Desarrollo, 2019)
For disarticulation between government agencies and the rural population, which has produced the need of create a new strategy of strengthening for the few producers of Papa Criolla from Subachoque- Cundinamarca. This has allowed to play the important role of leadership with a high level in this field, which allows for the strengthening of organizational, productive, economic, social and human strengthening, in favor of modern, profitable and sustainable agricultural practices that helps the productive chains of the goods of this productive sector.The work that has been done in this investigation, allowed to found out the main problems that affects the small producer from Subachoque and the facts that will make those workshops stronger than they are by now, whit the purpose of being able to establish parameters that solve them to the shortcomings present in the current productive field. Also, they came up with the idea of a new route that will bring better conditions focusing on the fields that produce more quantity of their product.
Keywords: Associativity; articulation; production fields; Papa Criolla